2019
DOI: 10.7759/cureus.5840
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Injury Following Thoracic Spinal Fusion for Adolescent Idiopathic Scoliosis

Abstract: Spinal fusion for adolescent idiopathic scoliosis (AIS) can have many potential complications, including spinal cord injury. Most often, spinal cord injury occurs in the region of surgery due to direct mechanical trauma. Vascular compromise in this area may also occur due to a high degree of correction or excessive distraction of the spine. In these cases, the impairment of spinal cord function is often detected intraoperatively with spinal cord monitoring and confirmed in the immediate postoperative period. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…following a red blood cell transfusion, the patient made a complete neurological recovery at one-year follow-up. samtani et al 39 reported a patient with ais whose weakness of the right arm after sugery with a myelomalacia was identified on MRI. The intraoperative blood loss was 500 ml.…”
Section: Discussionmentioning
confidence: 99%
“…following a red blood cell transfusion, the patient made a complete neurological recovery at one-year follow-up. samtani et al 39 reported a patient with ais whose weakness of the right arm after sugery with a myelomalacia was identified on MRI. The intraoperative blood loss was 500 ml.…”
Section: Discussionmentioning
confidence: 99%